The Role of Entrepreneurship Education in Increasing Entrepreneurial Motivation - Alvien Khardin; Muhammad Giatman; Yuliana (Enrichment : Journal of Management, 2022)
The purpose of this study will be to examine the role of entrepreneurship education in increasing entrepreneurial motivation. The results of this study are expected to be input for the development of entrepreneurship education in schools and universities in order to encourage the birth of intellectuals who choose a career as an entrepreneur (entrepreneur). In the end, with the increasing number of school graduates and undergraduates who choose to become entrepreneurs, the problem of limited employment opportunities can be resolved, so that it is hoped that economic development in Indonesia will continue to increase and advance. The method used in this study is to use a literature review. The results of this study are (1) entrepreneurship education is a process or activity carried out in order to internalize the entrepreneurial mentality, transmit entrepreneurial knowledge and skills to students through formal educational institutions (schools and universities) and non-formal institutions (training institutions) in an effort to take advantage of business opportunities. (2) entrepreneurial motivation is the driving force that makes someone do a new business as a long-term career. The driving force can come from within, such as intentions and desires, or from outside, such as advice, suggestions and input. (3) entrepreneurship education plays a very important role in increasing entrepreneurial motivation.